9th Grade Students' Learning of Designing an Incubator through Instruction Based on Engineering Design Tasks - Fethiye Karsli Baydere; Aydın Murat Bodur (Journal of Science Learning, 2022)
In this study, a STEM activity was designed in which 9th-grade students can complete the task of making incubators by overcoming the difficulties they face in the engineering design process. This activity has been handled in the context of energy conversion and prepared based on the engineering design process consisting of 9 stages. The activity was applied to 34 (19 females and 15 males) 9th-grade students studying at a public school in the Eastern Black Sea Region in Turkey in the fall semester of the 2019-2020 academic year. This application took 7 lesson hours (7x40 minutes) in total. At each stage of the engineering design process, students worked like an engineer and scientists by collaboratively conducting scientific research and inquiry. Throughout the process, students were confronted with several difficulties, given the time and opportunity to help them develop STEM literacy. More importantly, the students had the opportunity to experience a STEM activity by putting the steps of the engineering design process into practice.